A microwave doppler technique for vehicle speed determination - Martin, Neil Cameron (Department of Electrical Engineering, 2016)
Conventional Microwave Doppler Speed Measurement systems have long been considered unusable in many situations. In this dissertation a novel technique for speed measurement is presented which eliminates some of the problems associated with conventional systems, in particular the problem of vehicle identification. It is shown how a 'capture area' may be defined. Only the speeds of vehicles within the capture area are measured. A prototype speed measuring instrument was designed and constructed. The instrument was shown to work as predicted and the the notion of the 'capture area' was proved.